Cockayne Syndrome Misdiagnosed as Cerebral Palsy - VAFAEE, Amiereza (Iran J Child Neurol, 2018)
A 7-yr-old patient was referred to pediatric orthopedic clinic of Imam hospital (2016) with the diagnosis of cerebral palsy (CP). His parents were concerned about some inconsistency of his disease progression. After initial evaluations, the diagnosis of CP was incorrect. The true diagnosis was suspected and confirmed with molecular genetic analysis. A rare autosomal recessive disorder -Cockayne syndrome- was diagnosed. Although untreatable, it can be prevented by appropriate prenatal diagnostic tests for their future children.